2012
DOI: 10.1007/s00284-012-0250-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Bacteria Isolated from Rhabditis sp. (Nematoda) and Identification of Novel Entomopathogenic Serratia marcescens Strains

Abstract: Twenty-five bacterial strains isolated from entomopathogenic nematodes were characterized to the genus level by 16S rRNA phylogeny and BLAST analyses. Bacteria strains isolated could be affiliated with seven genera. Microbacterium-like isolates phylogenetically affiliated with M. oxydans while those of Serratia were highly similar to S. marcescens. 16S rRNA sequences of Bacillus isolates matched those of both B. mycoides and B. weihenstephanesis. One isolate each matched Pseudomonas mosselii, Rheinheimera aqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…putida group, was first described by Dabboussi et al (2002) as having rod-shaped cells producing a fluorescent pigment. The bacteria is an environmental (Naik et al 2008) and recently, was isolated from entomopathogenic nematodes (Tambong 2013). Overall, this bacterium is an unusual human opportunistic pathogen (Mclellan and Partridge 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…putida group, was first described by Dabboussi et al (2002) as having rod-shaped cells producing a fluorescent pigment. The bacteria is an environmental (Naik et al 2008) and recently, was isolated from entomopathogenic nematodes (Tambong 2013). Overall, this bacterium is an unusual human opportunistic pathogen (Mclellan and Partridge 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria is an environmental species detected mainly in rhizospheric soil (Naik et al . ) and recently, was isolated from entomopathogenic nematodes (Tambong ). Overall, this bacterium is an unusual human opportunistic pathogen (Mclellan and Partridge ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serratia marcescens strains used in this study were isolated and identified as indicated in Tambong (2013). Briefly, samples of dead bark of red oak tree (Quercus rubra L.) were collected from a woodland near Charleston Lake, southern Ontario, Canada.…”
Section: Bacteria Used and Pathogenicity To G Mellonellamentioning
confidence: 99%
“…Some reports have shown that the some species of intestinal bacteria associated with rhabditid nematodes could serve to promote nematode biological control effects. Nineteen bacterial genera have been found to be mutually associated with Rhabditis (Oscheius) nematodes: Bacillus (Mohandas et al, 2007), Klebsiella, Acinetobacter, Comamonas, Brucellaceae, Achromobacter (Deepa, Mohandas, & Siji, 2011), Alcaligenes, Flavobacterium, Providencia (Park, Kim, Ha, & Youn, 2011), Stenotrophomonas, Enterobacter, Proteus, Pseudomonas, Enterococcus, Lysinibacillus (Padmakumari et al, 2007Sangeetha et al, 2016), Microbacterium, Serratia, Rheinheimera and Staphylococcus (Tambong, 2013). Among them, Bacillus cereus isolate 03BB102 (Mohandas et al, 2007), Flavobacterium sp., Providencia vermicola (Deepa et al, 2011), Serratia marcescens (Tambong, 2013) and Serratia nematodiphila (Zhang, Yang, Xu, & Sun, 2009) exhibit virulence against insects and help improve nematode reproduction.…”
mentioning
confidence: 99%